The ontological and phenomenological dimensions of the concept of environment in questioning thought in Martin Heidegger - Louazani, Khira; Mahmoudi, Khelifa (The International tax journal, 2025)
Martin Heidegger expressed a dual concern with the concept of the environment in his inquiry into the meaning of thought. He approached this through a phenomenological analysis and an ontological interpretation that together reveal the environment's role in the ontological constitution of being—a being that is always defined within a specific world. In its effort to affirm existence, being emerges from the lived world, which sets the parameters for the awareness of being. Each subject, in turn, defines its environment as a mode of thinking. Thus, the environment of thought becomes the secure path through which the subject moves toward being. In this sense, thinking becomes a kind of geography from which the subject derives its existence and realises its actual fulfilment.